Energy transfer based emission analysis of Eu3+doped Gd2O3-CaO-SiO2-B2O3glasses for laser and X-rays detection material applications - N. Wantana (2018)
© 2017 Elsevier B.V. The Eu 3+ -doped CaO-Gd 2 O 3 -SiO 2 -B 2 O 3 glasses were prepared to study photoluminescence, lasing potential and scintillation properties. Glasses absorb photons in ultraviolet, visible light and near infrared regions and are assigned to the energy transitions of Gd 3+ and Eu 3+ . Ultraviolet with 275 nm can generate the strong red emission with 614 nm via energy transfer form Gd 3+ to Eu 3+ . X-ray scintillation study exhibits strong emission pattern due to Gd-Eu energy transfer. The optimum concentrations of Eu 3+ ion in this glass is 0.30 mol% as it results maximum emission intensity. The fluorescence lifetime of the 5 D 0 level decreases from 1.763 to 1.726 ms when concentration increased from 0.05 to 0.40 mol%. From Judd-Ofelt analysis, this glass exhibit high potential for using as laser medium for red laser device with high lasing power and energy extraction ratio. Moreover, this glass performs the integral scintillation efficiency as 13% compared with BGO.